Physical properties of Sn58Bi-xNi lead-free solder and its interfacial reaction with copper substrate - Kanlayasiri, Kannachai (Elsevier, 2015)
The aims of this research are to investigate the effects of Ni on the physical properties of Sn58Bi-xNi lead-free solder, and to examine its interfacial reaction with the copper substrate. In the experiments, four concentrations of Ni (i.e. 0.05, 0.1, 0.5 and 1.0 wt.%) were individually added into Sn58Bi and their respective microstructure, tensile strength, elongation, melting temperature, wettability and electrical resistivity of Sn58Bi-xNi were subsequently measured. The results indicated that Ni refined the microstructure of the solder matrix and induced the formation of Ni3Sn4 intermetallic phase, and that the size and volume fraction of Ni3Sn4 were positively correlated to the Ni content. The optimal concentration of Ni to enhance the tensile strength of the alloy was 0.1 wt.%, but the elongation of the alloy was inversely correlated to the Ni content. The addition of Ni contributed positively to the melting temperature and wetting behavior of the alloy, whereas no significant change in the electrical resistivity of Sn58Bi-xNi was detected. In addition, Ni increased the thickness of the intermetallic layer at the interface, and only monoclinic eta-Cu6Sn5 phase was present at the intermetallic layer. Nevertheless, the intermetallic phase of this research was dissimilar from the findings of existing literature. (C) 2015 Elsevier Ltd. All tights reserved.